A Patient with Chronic Lymphocytic Leukemia with Pancreatic Involvement - Rajesh Essrani; Matthew J. Sullivan; Hiral Shah (Case Reports in Hematology)
A 78-year-old female with a past medical history of hypertension, type 2 diabetes mellitus, and chronic lymphocytic leukemia was hospitalized for poor appetite, weight loss, and night sweats. On physical exam, there was no palpable lymphadenopathy, and her abdomen was soft and nondistended. Laboratory results showed a hemoglobin count of 13.3 g/dl, hematocrit 41.3%, white blood cell 68.4 × 103 μL with lymphocytes 92.0%, total bilirubin 0.4 mg/dL, aspartate transaminase 14 U/L, and alanine transaminase 15 U/L. CT of the chest, abdomen, and pelvis showed hypodense lesions within the pancreatic body (1.4 × 1.4 cm) and medial aspect of the pancreatic head (1.2 cm) as well as mild splenomegaly (13 cm craniocaudally). She subsequently underwent endoscopic ultrasound (EUS) with fine needle aspiration (FNA) of the pancreatic mass. Flow cytometry revealed expression of CD5 and CD23, consistent with chronic lymphocytic leukemia.